Ownership concentration effect on market sentiment and corporate social responsibility performance in selected asian countries - Mitra, Aditi (2019)
Investors have been a neglected stakeholder group in studies on firm’s motivations to be socially and environmentally responsible. Despite being a strong driving force behind capital support, there is scarcity of studies investigating the influence of market sentiments on firms’ CSR performance. Alongside, the phenomenon of corporate social responsibility (CSR) is gaining significance in Asian economies, as these markets are undergoing rapid economic growth coupled with various types of societal challenges and driven by increased business activities. There are expectations that Asian business will come up with solutions to many of the twenty-first century’s social and environmental challenges, such as water accessibility, global warming, climate change, and affordable health care in order to keep up with the growth momentum. Investors’ concerns about credible CSR information questions the degree of information asymmetry that exists among investors and firms, as well as the nature of CSR in Asian countries, particularly in situations where firms tend to have concentrated ownership. Concentrated ownership encourages firms in Asia to divert the socially responsible investments (SRIs) coming from investors towards personal gains. The distinct contexts of economic, social and ownership structure make it an appropriate environment for comparison between developed and developing markets from within the Asian countries to examine the relationship between market sentiment and CSR performance. Malaysia and Thailand are the two selected developing countries in this study which are undergoing rapid economic growth, thus, a good market to attract SRIs from global investors. Similarly, Singapore and Hong Kong are the chosen developed Asian countries in this study which have seen considerable economic growth and development; thus, a good case to use for studying CSR performance. This study employs Information Economics theory and Agency theory where the central premise is that firm’s trade off the related benefits and costs in their decisionmaking about the level of engagement between investors and CSR performance compliance. Accordingly, concentrate ownership leads firms to make effective decisions and maximise benefits of their decisions about the value of stakeholder engagement prior to undertaking CSR performance. This study provides an empirical investigation in the developed and developing Asian market context, and proposes a conceptual framework consisting of three variables that potentially influence the nature of CSR in Malaysia, Singapore, Hong Kong and Thailand. These variables include market sentiment, ownership concentration and CSR performance in individual dimension (environment, social and governance). In addition to emphasizing the context in which CSR is conceptualized and practiced, this thesis also builds a theoretical foundation that aids in the development of CSR debates, in particular, the sub-parameters of CSR influencing value maximisation goal of the firm and the future implementation of CSR in these markets. This study employs a quantitative research design and the findings of this study are based on the analyses of 7,140 firm observations from the chosen Asian markets. This study finds a positive and significant relationship between market sentiment and CSR performance. It also finds that this relationship differs across the CSR performance sub-dimensions (i.e., environment, social, governance and total performance) among firms in the chosen markets, indicating the significance of disclosing detailed CSR performance compliance as a measure to reduce information asymmetry, as opposed to an aggregate or total CSR performance level. Finally, the study finds that there is a significant moderating effect of ownership concentration on the relationship between market sentiment and CSR performance. This study constructs a usable countryspecific market sentiment index that can be used for capital investment decisions among firms. The results of this study provide empirical evidence to fill the gap in the knowledge by incorporating the information economics theory and agency theory constructs in a competing way. The findings of this study aim to address the on-going concerns of the investors seeking credible CSR performance information from the firms. Further, the long-standing debate over whether CSR performance enhances the long-term value of firms or not is also discussed in this thesis. Finally, the results imply that standard setters and regulators should seek to persuade firms to engage with investors to strategize CSR related investments prior to undertaking the actual CSR initiatives.